Unheard voices as “counter narratives”: Digital storytelling as a way of empowering Muslim women - Mai Mowafy (Indonesian Journal of Applied Linguistics, 2022)
The paper investigates the use of digital storytelling as a means of empowering Muslim women and enabling them to be heard. It examines how digital stories are used as “counter narratives” by Muslim women to refute public dominant narratives as “counter-narratives” resist stereotypes and taken-for-granted assumptions. “Narrating” or “storytelling” is a powerful mode that can be used in the struggle of changing stereotypes. Currently, in the digital era where we live, stories are narrated digitally using digital tools. Digital stories by Muslim women are refuting “dominant public narratives” and establishing a new “master narrative” of their own that challenges the stereotypes. The study applies an eclectic approach that draws on “multimodal discourse analysis”, “narrative theory” and the previous studies. It analyzes five digital stories by Muslim women and highlights the verbal and non-verbal strategies used to counter dominant public narratives. Based on the multimodal discourse analysis conducted, the study finds that digital stories construct a new “master narrative” through the use of various verbal and non-verbal strategies to counter dominant “public narratives”. As such the study proved that digital stories are used as a powerful tool for empowering Muslim women in refuting misconceptions and creating a better future where diversity and acceptance can prevail.